Impact of the Advent of Collagenase Clostridium Histolyticum on the Surgical Management of Peyronie's Disease: A Population-Based Analysis. Issue 1 (21st November 2019) - Sukumar, Shyam; Pijush, Debduth Bardhan; Brandes, Steven
Abstract: Introduction: Penile plication or partial excision with grafting has traditionally been the first-line treatment for stable Peyronie's disease (PD). Numerous injection therapies (ITs) have been introduced over the last few decades. Intralesional collagenase clostridium histolyticum (CCH) was U.S. Food and Drug Administration approved in 2013 for patients with stable disease, curvature ≥30° and ≤90°, and intact erectile function. The impact of the advent of CCH on the surgical management of PD is unknown. Aim: We studied the effect of IT on the surgical management of PD in a population-based analysis. Methods: The Statewide Planning and Research Cooperative System database, which provides statewide level of all-payer data on patients in the outpatient, inpatient, ambulatory, and emergency department setting in New York State was reviewed. Patients undergoing a penile prosthesis for concurrent erectile dysfunction were excluded. Main Outcome Measure: Descriptive statistics and multivariable logistic regression modeling were used to assess factors influencing choice of injection therapy vs surgical therapy (penile plication or partial excision with grafting). Results: From 2003−2016, 547 patients with PD presented for management. Median age was 56 years and 57% were white. Over the study period, surgical management was used less often as the primary procedure with a concurrent increase in use of IT ( P < .001). On multivariable modeling, patients more likely to receive IT as treatment for penile curvature were younger (odds ratio [OR]: 1.26; P = .002; CI: 1.09−1.46), of higher socioeconomic status (OR: 1.14; P = .037; CI: 1.01−1.29), presented in the post-CCH era (OR: 1.17; P = .018; CI: 1.03−1.33) and presented to a surgeon with a high volume practice (OR: 1.25; P = .007; CI: 1.07−1.48). Patients presenting in the post-CCH era were 17% significantly more likely to receive IT. Clinical Implications: ITs like CCH are increasingly displacing surgical management as the primary treatment option of Peyronie's disease. Strengths & Limitations: The Statewide Planning and Research Cooperative System database is particularly useful for this analysis because it is an all-payer database that tracks patients longitudinally across various health care settings—outpatient and inpatient. Limitations: It only includes patients in New York State limiting generalizability. The retrospective nature of the analysis makes it subject to the biases inherent in such reports. Specific disease level characteristics (eg, degree of curvature, duration of disease, and associated deformities) were not available. Conclusion: Since the introduction of CCH, there has been a markedly decreasing trend in the utilization of surgery as the primary modality in the management of PD-associated penile curvature.